Prospective memory in first-degree relatives of patients with schizophrenia. Issue 5 (4th July 2018) - Saleem, Saima; Kumar, Devvarta; Venkatasubramanian, Ganesan
Abstract: Objectives: Among various cognitive impairments in schizophrenia, prospective memory (ProM) deficit is unequivocally established. However, there is a paucity of research examining whether ProM impairment can be considered a cognitive endophenotypic marker in schizophrenia. An important step toward this is to assess the status of ProM in first-degree relatives (FDRs) of patients with schizophrenia. Keeping this in view, present study has been conducted to assess event- and time-based ProM in FDRs of patients with schizophrenia.Methods: Twenty patients with schizophrenia, 20 FDRs of these patients, and 20 nonpsychiatric (healthy) controls were administered event- and time-based ProM tasks.Results: Findings show that the FDRs had poorer performance on event-based ProM task in comparison to healthy controls. On time-based task, though the FDRs performed poorly in comparison to healthy controls the difference was statistically non-significant. The patient group performed poorer than healthy controls on both event- and time-based tasks.Conclusions: Findings of the present study indicate that the FDRs of patients with schizophrenia exhibit ProM impairment, though to a lesser degree than the patients with schizophrenia.